Binomial Coefficient Pattern

( p 1 q ) , ( p 2 q ) , ( p 3 q ) , \dbinom{p_1}{q}, \dbinom{p_2}{q}, \dbinom{p_3}{q}, \ldots Here, p n p_n represents the infinite arithmetic sequence of the strictly increasing integers, such that for each positive n n , p n > q p_n > q . q q is a fixed positive integer throughout the sequence.

Which of the given sequences does the above best represent?

Notation: ( n k ) = n ! k ! ( n k ) ! \dbinom{n}{k} = \dfrac{n!}{k!(n - k)!} denotes the binomial coefficient .

Arithmetic progression Harmonic progression Geometric progression

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Michael Huang
Dec 11, 2016

Let a n = ( p n q ) a_n = \dbinom{p_n}{q} For the proof, let b , c b,c denote arbitrary positive integers, such that b < c b < c .


Arithmetic Progression

If a n a_n is the arithmetic progression, then a c = a b + ( c b ) × d a_c = a_b + (c - b) \times d

which shows that the following must hold a b + a c b = a c a_b + a_{c - b} = a_c Evaluating, ( p b q ) + ( p c b q ) = ( p c q ) ( p b ) ! q ! ( p b q ) ! + ( p c b ) ! q ! ( p c b q ) ! = ( p c ) ! q ! ( p c q ) ! By definition ( p b ) ! q ! ( p b q ) ! + ( p c b ) ! q ! ( p c b q ) ! = ( p c ) ! q ! ( p c q ) ! Multiply both sides by q ! \begin{array}{rlccl} \dbinom{p_b}{q} + \dbinom{p_{c - b}}{q} &= \dbinom{p_c}{q}\\ \dfrac{\left(p_b\right)!}{q!\left(p_b - q\right)!} + \dfrac{\left(p_{c - b}\right)!}{q!\left(p_{c - b} - q\right)!} &= \dfrac{\left(p_c\right)!}{q!\left(p_c - q\right)!} & & & {\color{#3D99F6}\text{By definition}}\\ \dfrac{\left(p_b\right)!}{q!\left(p_b - q\right)!} + \dfrac{\left(p_{c - b}\right)!}{q!\left(p_{c - b} - q\right)!} &= \dfrac{\left(p_c\right)!}{q!\left(p_c - q\right)!} & & & {\color{#3D99F6}\text{Multiply both sides by }q!} \end{array} Either q = 1 q = 1 or q > 1 q > 1 .

Case 1

If q = 1 q = 1 , then p b + p c b = p c p b + ( c b ) d p = p c \begin{array}{rl} p_b + p_{c - b} &= p_c\\ p_b + \left(c - b\right)d_p &= p_c \end{array} which satisfies the given that p n p_n is an arithmetic progression. Therefore, a n a_n is an arithmetic progression.

Case 2

Otherwise, q > 1 q > 1 , which however violates that p n p_n is an arithmetic progression. Consider ( p b ) ! ( p b q ) ! + ( p c b ) ! ( p c b q ) ! = ( p c ) ! ( p c q ) ! \dfrac{\left(p_b\right)!}{\left(p_b - q\right)!} + \dfrac{\left(p_{c - b}\right)!}{\left(p_{c - b} - q\right)!} = \dfrac{\left(p_c\right)!}{\left(p_c - q\right)!} Evaluating, p b × ( p b 1 ) × × ( p b q + 1 ) + p c b × ( p c b 1 ) × × ( p c b q + 1 ) = p c × ( p c 1 ) × × ( p c q + 1 ) p_b \times \left(p_b - 1\right) \times \dots \times \left(p_b - q + 1\right) + p_{c - b} \times \left(p_{c - b} - 1\right) \times \dots \times \left(p_{c - b} - q + 1\right) = p_c \times \left(p_c - 1\right) \times \dots \times \left(p_c - q + 1\right) which is impossible to express in the closed arithmetic form for q > 1 q > 1 since there occurs multiple p p 's after expanding the above equation. We can also note that by expanding and comparing both sides, p b × ( p b 1 ) × × ( p b q + 1 ) + p c b × ( p c b 1 ) × × ( p c b q + 1 ) < p c × ( p c 1 ) × × ( p c q + 1 ) p_b \times \left(p_b - 1\right) \times \dots \times \left(p_b - q + 1\right) + p_{c - b} \times \left(p_{c - b} - 1\right) \times \dots \times \left(p_{c - b} - q + 1\right) < p_c \times \left(p_c - 1\right) \times \dots \times \left(p_c - q + 1\right)


Geometric Progression

If this were to be true, then a c = a b × r c b a_c = a_b \times r^{c - b} where r > 1 r > 1 . If q = 1 q = 1 , then p c = p b × r c b p_c = p_b \times r^{c - b} where r = ( p c p b ) 1 c b r = \left(\dfrac{p_c}{p_b}\right)^{\frac{1}{c - b}} . If suppose we let e e be the positive integer, such that e b , c e \neq b,c , p e = p b × r e b p_e = p_b \times r^{e - b} However, p b × ( p c p b ) e b c b = p e = p b + p e b \begin{array}{rl} p_b \times \left(\dfrac{p_c}{p_b}\right)^{\frac{e - b}{c - b}} &= p_e\\ &= p_b + p_{e - b} \end{array} which shows that this cannot happen since p n p_n is arithmetic. If q > 1 q > 1 , a n a_n can't be geometric by the similar reasoning.


Harmonic Progression

Because p n p_n is an arithmetic sequence of strictly increasing integers, a n a_n is increasing as well. Thus, it impossible for a n a_n to be harmonic for arbitrary p p 's and q q 's.


Conclusion

( 2 1 ) , ( 4 1 ) , ( 6 1 ) , ( 8 1 ) , , ( 2 + 2 d 1 ) , \dbinom{2}{1}, \dbinom{4}{1}, \dbinom{6}{1}, \dbinom{8}{1}, \dots, \dbinom{2 + 2d}{1}, \dots If p n p_n is arithmetic progression, so is a n a_n . However, this only works for p = 1 p = 1 . There is no other way for a n a_n to be arithmetic for any other p p .

Likewise, if p n p_n is geometric progression, so is a n a_n for p = 1 p = 1 . Proving this is routine, which is much like how arithmetic progression is determined for this problem.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...